PERBANDINGAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DAN TEAMS GAME TURNAMENT (TGT) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VII SMP (STUDI EKSPERIMEN DI SMP NEGERI 1 PURWOJATI) KECAMATAN PURWOJATI KABUPATEN BANYUMAS TAHUN PELAJARAN 2018/2019: Array - Fasha, Eka Farida; Prihastuti, Ika Nur (Jurnal Dialektika Program Studi Pendidikan Matematika, 2019)
The purpose of this study are 1) To find out the mathematics learning outcomes of students with the Jigsaw type cooperative learning model and the Team Games Tournament (TGT) type of cooperative learning model whether it will be better than conventional learning models. 2) To find out the average learning outcomes with the type of jigsaw cooperative learning model and Team Games Tournament (TGT) students can reach the KKM. Jigsaw and TGT type of cooperative learning model is one type of cooperative learning that places students in learning groups of 5-8 people who have different abilities, genders and ethnicities or races. The method used in this research is the experimental method. The population in this study were all VII grade students of SMP Negeri 1 Purwojati in the 2018-2019 school year, totaling 221 students. Of the seven classes, three classes were randomly selected as research samples, namely class VII E which was treated as a jigsaw class, class VII F as a conventional class and VII G as a TGT class. The results of data analysis show that: 1) Mathematics learning outcomes of Grade VII students of SMP Negeri 1 Purwojati taught using the Jigsaw learning model are relatively high with an average value of 81.281 of 32 students. 2) Mathematics learning outcomes of Grade VII students of SMP Negeri 1 Purwojati taught using the TGT learning model are relatively high with an average value of 78.781 out of 32 students.